Have the tax benefits of debt been overestimated? - Blouin, Jennifer; Core, John E.; Guay, Wayne (Journal of Financial Economics, 2010)
We re-examine the claim that many corporations are underleveraged in that they fail to take full advantage of debt tax shields. We show prior results suggesting underleverage stems from biased estimates of tax benefits from interest deductions. We develop improved estimates of marginal tax rates using a non-parametric procedure that produces more accurate estimates of the distribution of future taxable income. We show that additional debt would provide firms with much smaller tax benefits than previously thought, and when expected distress costs and difficult-to-measure non-debt tax shields are also considered, it appears plausible that most firms have tax-efficient capital structures.